Prevalence and variability of current depressive disorder in 27 European countries: a population-based study - Jorge Arias-de la Torre, PhD; Gemma Vilagut, PhD; Amy Ronaldson, PhD; Antoni Serrano-Blanco, ProfPhD; Vicente Martín, ProfPhD; Michele Peters, ProfPhD; Jose M Valderas, ProfPhD; Alex Dregan, PhD; Jordi Alonso, ProfPhD (Elsevier, 2021)
Summary: Background: We aimed to estimate the prevalence of current depressive disorder in 27 European countries, and to explore differences in prevalence between European countries and by gender. Methods: In this population-based study, we analysed data from respondents living in 27 European countries who were included in the second wave of the European Health Interview Survey, collected between 2013 and 2015. We assessed the prevalence of current depressive disorder using the eight-item Patient Health Questionnaire (PHQ-8), with depressive disorder defined as a PHQ-8 score of 10 or higher. Prevalence estimates and 95% CIs were calculated for all 27 countries overall and for each country individually. We assessed variation in prevalence (country vs the rest of Europe) using crude and adjusted prevalence ratios obtained from negative binomial regression models. We did all analyses for the total sample and stratified by gender. Findings: Our analysis sample comprised 258 888 individuals, of whom 117 310 (weighted proportion 47·8%) were men and 141 578 (52·2%) were women. The overall prevalence of current depressive disorder was 6·38% (95% CI 6·24-6·52) with important variation across countries, ranging from 2·58% (2·14-3·02) in the Czech Republic to 10·33% (9·33-11·32) in Iceland. Prevalence was higher in women (7·74% [7·53-7·95]) than in men (4·89% [4·71-5·08]), with clear gender differences for all countries except Finland and Croatia. Compared with the other European countries in our sample, those with the highest adjusted prevalence ratios were Germany (1·80 [1·71-1·89]) and Luxembourg (1·50 [1·35-1·66]), and those with the lowest adjusted prevalence ratios were Slovakia (0·28 [0·24-0·33]) and the Czech Republic (0·32 [0·27-0·38]). Interpretation: Depressive disorders, although common across Europe, vary substantially in prevalence between countries. These results could be a baseline for monitoring the prevalence of current depressive disorder both at a country level in Europe and for planning health-care resources and services. Funding: UK Medical Research Council and CIBER Epidemiology and Public Health (CIBERESP).